ANALISIS BUDAYA KERJA PEGAWAI BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL PROPINSI SULAWESI TENGAH - Kushindarwito, Kushindarwito (Katalogis, 2016)
This research aims at describing the application of work culture of the employees at the representative office of civil statistic and family planning, central Sulawesi. This research used descriptive qualitative method. The data were collected through observation, interview, and documentation. The seven informans were collected through purposive sample.The results showed that the application of work culture of the employees were still not optimal or low.Based on the indicator of work culture proposed by Robbin, the results showed that the application of work culture value of the employee at the representative office population board and family planning, central Sulawesi are influenced by some aspects, such as: 1) honesty, 2) perseverance, 3) creativity, 4) discipline, 5) responsibility. It can be concluded that the application of work culture of the employee are still not optimal or low based on those five indicators.